2016
DOI: 10.3748/wjg.v22.i37.8304
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of laparoscopic colorectal resection for cancer: What is the impact on short-term outcomes and survival?

Abstract: Laparoscopic resection for colon and rectal cancer is associated with quicker return of bowel function, reduced postoperative morbidity rates and shorter length of hospital stay compared to open surgery, with no differences in long-term survival. Conversion to open surgery is reported in up to 30% of patients enrolled in randomized control trials comparing open and laparoscopic colorectal resection for cancer. In this review, reasons for conversion are anatomical-related factors, disease-related-factors and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 43 publications
6
38
2
2
Order By: Relevance
“…The readmission rate of 9.8% is not exceeding readmission rates in reports with longer primary LoS [22,23] and hence seems acceptable, reflecting an overall reasonable discharge policy. The conversion rate of 10.2% of all commenced laparoscopy is in line with recent reports from other unselected cohorts [24,25].…”
Section: Discussionsupporting
confidence: 90%
“…The readmission rate of 9.8% is not exceeding readmission rates in reports with longer primary LoS [22,23] and hence seems acceptable, reflecting an overall reasonable discharge policy. The conversion rate of 10.2% of all commenced laparoscopy is in line with recent reports from other unselected cohorts [24,25].…”
Section: Discussionsupporting
confidence: 90%
“…[2] Various studies have shown that the need to convert from laparoscopic to open surgery may emerge due to factors, such as advanced age, high ASA class (≥III or IV), high BMI, male gender, history of abdominal surgery, local advanced neoplasia, middle and lower rectal cancers, and complicated diverticulitis. [1,4,10,11] In the current study, BMI was ≥28 in most of the patients that required open surgery conversion, with male gender, age and tumor invasion being present at lower rates in this group. Among the reasons for conversion, difficulty of exploration and history of surgery were more frequent.…”
Section: Discussionmentioning
confidence: 52%
“…Studies suggest that BMI, local tumor invasion, and comorbidities are independent risk factors of conversion to open surgery. [4] In the literature, it has been reported that the conversion rate is increased in cases above 65 years, those with a BMI of ≥28, male patients, and in the presence of tumor invasion. [2] Various studies have shown that the need to convert from laparoscopic to open surgery may emerge due to factors, such as advanced age, high ASA class (≥III or IV), high BMI, male gender, history of abdominal surgery, local advanced neoplasia, middle and lower rectal cancers, and complicated diverticulitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the most frequent reason for conversion was invasion of cancer to adjacent tissues or organs, which accounts for nearly 50%. Allaix et al [16] reviewed all literature on cases of open conversion during laparoscopic resection for both colon cancer and rectal cancer for all years up to March 2016, and the most frequent reasons for conversion were also cancer-related factors. The other causes they reported were adhesion, obesity, or anatomic-related factors, which were similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%